Drosophila RSK Influences the Pace of the Circadian Clock by Negative Regulation of Protein Kinase Shaggy Activity - Beck, Katherina; Hovhanyan, Anna; Menegazzi, Pamela; Helfrich-Förster, Charlotte; Raabe, Thomas (Frontiers in Molecular Neuroscience, 2018)
Endogenous molecular circadian clocks drive daily rhythmic changes at the cellular, physiological, and behavioral level for adaptation to and anticipation of environmental signals. The core molecular system consists of autoregulatory feedback loops, where clock proteins inhibit their own transcription. A complex and not fully understood interplay of regulatory proteins influences activity, localization and stability of clock proteins to set the pace of the clock. This study focuses on the molecular function of Ribosomal S6 Kinase (RSK) in the Drosophila melanogaster circadian clock. Mutations in the human rsk2 gene cause Coffin-Lowry Syndrome, which is associated with severe mental disabilities. Knock-out studies with Drosophila orthologue rsk uncovered functions in synaptic processes, axonal transport and adult behavior including associative learning and circadian activity. However, the molecular targets of RSK remain elusive. Our experiments provide evidence that RSK acts in the key pace maker neurons as a negative regulator of Shaggy (SGG) kinase activity, which in turn determines timely nuclear entry of the clock proteins Period and Timeless to close the negative feedback loop. Phosphorylation of serine 9 in SGG is mediated by the C-terminal kinase domain of RSK, which is in agreement with previous genetic studies of RSK in the circadian clock but argues against the prevailing view that only the N-terminal kinase domain of RSK proteins carries the effector function. Our data provide a mechanistic explanation how RSK influences the molecular clock and imply SGG S9 phosphorylation by RSK and other kinases as a convergence point for diverse cellular and external stimuli.